Impact of Sambas Besar Bridge on Tebas Intersection Performance, West Kalimantan - Sarah, Siti; Azwansyah, Heri; Kadarini, Siti Nurlayli (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
The operation of the Sambas Besar Bridge (JSSB) significantly alters traffic patterns around Tebas District, particularly at the unsignalized Tebas three-way intersection, which serves both residential and commercial activities. This study applies the Indonesian Road Capacity Guidelines (PKJI, 2023) and microscopic simulation using VISSIM. Data collection included traffic volume surveys, geometric measurements, and vehicle counts using CCTV-based technology. Simulation parameters were validated against field conditions to ensure reliability. In 2025, the intersection was categorized as LOS B (delay = 9.4 seconds). Projections indicate declining performance, with LOS C expected to be reached by 2040 if no intervention is applied. Among the three evaluated improvement scenarios, the combined solution of road widening and median addition reduced the average delay to 10.86 seconds (LOS B). The research highlights how newly commissioned infrastructure influences secondary intersections. The proposed integrated solution demonstrates a sustainable strategy to maintain intersection service quality up to 2040, offering insights for other rapidly growing semi-urban regions.